A Sheep Model for Cancellous Bone Healing - Malhotra, Angad; Pelletier, Matthew Henry; Yu, Yan; Christou, Chris; Walsh, William Robert (Frontiers in Surgery, 2014)
Appropriate, well characterized bone defect animal models remain essential for preclinical research. This pilot study demonstrates a relevant animal model for cancellous bone defect healing. Three different defect diameters (8, 11, 14mm) of fixed depth (25mm) were compared in both skeletally immature (18 month old) and aged sheep (5 year old). In each animal, four defects were surgically created and placed in the cancellous bone of the medial distal femoral and proximal tibial epiphyses bilaterally. Animals were euthanized at four weeks post-operatively to assess early healing and any biological response. Defect sites were graded radiographically, and new bone formation quantified using µCT and histomorphometry. Fibrous tissue was found within the central region in most of the defects, with woven bone normally forming near the periphery of the defect. Bone volume fraction (BV/TV) significantly decreased with an increasing defect diameter. Actual bone volume (BV), however, increased with defect diameter. Bone ingrowth was lower for all defect diameters in the aged group. This pilot study proposes that the surgical creation of 11mm diameter defects in the proximal tibial and distal femoral epiphyses of aged sheep is a suitable large animal model to study early healing of cancellous bone defects. The refined model allows for the placement of four separate bone defects per animal, and encourages a reduction in animal numbers required for preclinical research.